KURIKULUM PENDIDIKAN ISLAM ANAK USIA DINI - Yusnani Batu Bara; Lydia Sartika (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
The education curriculum includes all activities in the learning environment that students will carry out under the guidance of education institutions , both in the clssroom and outside the classroom . curriculum is a very important thing inthe world of early childhood education , because reading and writing are the most important parts for realizing human development and progress. This is also reflected in the Al-Qur’an Surah Al- Alaq verse 1 which means read. The Islamic education curriculum in kindergarten is a series of educational activities in a fun way . The development of the curriculum in preschool is the activity of learning while playing , which can enrich children’s experiences in various ways, such as answering all questions from students , playing with nature, and so on .